2020
DOI: 10.1016/j.bbmt.2019.08.029
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3 Randomized Study of Remestemcel-L versus Placebo Added to Second-Line Therapy in Patients with Steroid-Refractory Acute Graft-versus-Host Disease

Abstract: Uncontrolled studies have suggested that bone marrow-derived mesenchymal stem cells (MSCs) may be effective against acute graft-versus-host disease (aGVHD). We conducted a multicenter, randomized study to assess the efficacy of using ex vivo cultured adult human MSC (remestemcel-L) in addition to second-line therapy to treat steroid-refractory aGVHD (NCT00366145). In total, 260 patients, 6 months to 70 years of age, were enrolled from August 2006 to May 2009 and were randomized 2:1 to receive 8 intravenous inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
127
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 29 publications
(41 reference statements)
5
127
0
Order By: Relevance
“…Results of this study confirm the overall response, safety, and survival demonstrated in a pediatric expanded-access program study that assessed remestemcel-L in children who failed to respond to steroids and additional immunosuppressive agents for the treatment of aGVHD [26,35]. In conclusion, MSB-GVHD001 and the MSB-GVHD002 follow-up study taken together with positive findings of other remestemcel-L studies in aGVHD [26,36,40] confirm the safety profile and demonstrate the efficacy and durability of remestemcel-L treatment for SR-aGVHD in the pediatric population.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Results of this study confirm the overall response, safety, and survival demonstrated in a pediatric expanded-access program study that assessed remestemcel-L in children who failed to respond to steroids and additional immunosuppressive agents for the treatment of aGVHD [26,35]. In conclusion, MSB-GVHD001 and the MSB-GVHD002 follow-up study taken together with positive findings of other remestemcel-L studies in aGVHD [26,36,40] confirm the safety profile and demonstrate the efficacy and durability of remestemcel-L treatment for SR-aGVHD in the pediatric population.…”
Section: Discussionsupporting
confidence: 77%
“…A number of factors are relevant to the experience reported in adults with aGVHD treated with MSCs, including variations in the type of design (prophylaxis versus treatment of GVHD), type of MSCs (adipose tissue, cord blood, or bone marrow derived cells), specific trial design elements (first line in new-onset GVHD, concomitant corticosteroids and MSCs after GVHD diagnosis, or established steroid refractory), choice of primary efficacy endpoint (the currently established day 28 overall response or durable complete response), choice or comparator, and specific aGVHD patient attributes such as severity of disease and organ involvement. The impact of several of these factors is described by Kebriaei et al [40]. In this randomized controlled trial of remestemcel-L versus placebo in both adults and children with aGVHD, among high-risk adult patients, remestemcel-L treatment produced significantly higher OR at day 28 compared with placebo (58% versus 37%; P = .03) and similarly improved day 28 OR compared with placebo in the pediatric subset (64% versus 23%; P = .05) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included in our meta-analysis a phase 3 randomized trial [43] of 260 patients (MSC = 163 patients, control = 81 patients) who did not receive other treatments than steroids before the randomization. This trial showed no differences for survival at day 180, and the OR was significantly higher for the MSC group in pediatric patients, patients with high-risk aGvHD and liver involvements.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis for OR and CR are summarized in Table S7 and S8, respectively (see Additional file, pp. [42][43]. No significant correlation was found between the proportion of responder patients and day of MSC infusion after HSCT ( Figure S21A) or MSC dose ( Figure S21B, pp.…”
Section: Mesenchymal Stromal Cells For the Treatment Of Steroidrefracmentioning
confidence: 96%